Intraductal lithotripsy in sialolithiasis with two different Ho:YAG lasers: presetting parameters, effectiveness, success rates. - Koch, Matthias; Hung, S. H.; Su, C. H.; Lee, K. S.; Iro, Heinrich; Mantsopoulos, Konstantinos (European Review for Medical and Pharmacological Sciences, 2019)
OBJECTIVE: To compare two different Ho:YAG laser systems in relation to the preset parameters and their effectiveness for intraductal fragmentation of the salivary stones. PATIENTS AND METHODS: We made a retrospective study in two tertiary referral centers (Department of ENT, Head and Neck Surgery, University of Erlangen-Nuremberg, Germany and the MacKay Memorial Hospital, Taipei, Taiwan). Patients with a diagnosis of sialolithiasis were treated in Erlangen and Taipei. The Erlangen patients were treated using the Calculase II™ Ho:YAG laser (Karl Storz, Tuttlingen, Germany) at 4 Hz, 1.2 J (4.8 W) and the MacKay patients were treated using the VersaPulse® PowerSuite™ Ho:YAG laser (Lumenis Ltd., Yokneam, Israel) at 6 Hz, 0.5 J (3 W). RESULTS: A total of 12 patients with 12 stones were treated in Erlangen and 54 with 75 stones in Taipei. The submandibular stones were present in 50% and 86.7% of cases, respectively. The complete fragmentation was achieved in all of the treated stones in both groups; 100% and 92.6% of the patients were stone-free, 100% and 94.4% of the patients became symptom-free, respectively. 33% of the Erlangen patients had multimodal treatments. The glands were preserved in all cases in both centers. CONCLUSIONS: The Ho:YAG laser proved to be effective in the treatment of sialolithiasis. Stone size, location, and involved gland were important additional parameters. Our experience and the literature results show that the laser presetting with a frequency of 3-6 Hz, an energy level of 0.5-1.2 J, and effective power of between 3 and 4.8 W is sufficient to achieve maximum success without any increased risk for complications.
EVALuna2:209872